Evaluating the understanding about kidney stones among adults in the United Arab Emirates - Hussain S. Aldaher; Safa Z. Kadhim; Nora M. Al-Roub; Ahmed H. Alsadi; Dana A. Salam; Eva A. Tillo (Journal of Taibah University Medical Sciences, 2021)
الملخص: أهداف البحث: تزايد انتشار حصى الكلى في جميع أنحاء العالم في العقد الماضي، ويُعتقد أن عوامل الخطر المتعددة تُعزى إلى التغيير في نمط الحياة، والنظام الغذائي، وحتى الاحتباس الحراري. في دولة الإمارات العربية المتحدة، لم يتم عمل الكثير من البحوث لاستكشاف انتشار حصى الكلى والمعرفة عنها. تهدف هذه الدراسة إلى قياس مدى معرفة المجتمع بحصى الكلى بين البالغين في دولة الإمارات العربية المتحدة. طرق البحث: في هذه الدراسة المقطعية، تم جمع البيانات باستخدام استبانة ذاتية الإدارة تم توزيعها علىخمسة مائة و خمسة عشر مشارك (٢٠-٤٩ عاما) من أبو ظبي ودبي وعجمان والشارقة. النتائج: من بين ٥٠٠ مشارك، بلغ متوسط مجموع درجات المعرفة ٥٦.٤٪. لم يكن هناك ارتباط بين المعرفة بين أولئك الذين عانوا من حصى الكلى والذين لم يصابوا بها. كان وجود تاريخ عائلي بتشخيص حصى الكلى يزيد من خطر الإصابة بحصى الكلى بمعدل ٢.٢٧. وأظهرت النتائج أن المشاركين الذين كان لديهم علامات وأعراض وتشخيص وعلاج حصى الكلى، كان لديهم مستوى جيد من المعرفة بعد تحليل مصدر المعرفة، ولكن كان هناك مستوى ضئيل من المعرفة بخصوص العوامل الغذائية المتعلقة بحصى الكلى. كان للإنترنت ووسائل الإعلام دور أكبر بضعفين من الأطباء في تثقيف السكّان. الاستنتاجات: استطاعت هذه الدراسة أن توضح أن سكّان الإمارات على دراية ببعض الجوانب المتعلقة بحصوات الكلى ولكن على غير دراية بشأن عوامل الخطر التبعية. وهذا يسلط الضوء على أهمية تعزيز التعليم من خلال الحملات الصحية. Abstract: Objectives: The prevalence of kidney stones is increasing worldwide. Multiple risk factors are believed to contribute to the development of kidney stones such as lifestyle, diet, and global warming. In the United Arab Emirates (UAE), there has been limited research exploring the prevalence and risk factors of kidney stones. This study attempts to assess the understanding and prevalence of kidney stones among adults in the UAE. Methods: In this cross-sectional study, data were collected using a self-administered questionnaire, distributed among 515 participants (20–49 years old) from Abu Dhabi, Dubai, Ajman, and Sharjah states. IBM SPSS version 25 was used for data analysis. Results: The mean of knowledge score was 56.4% (n = 500). There was no correlation between the knowledge of those who had experienced kidney stones and those who did not. Furthermore, a family history of kidney stones increased the risk of developing stones by 2.27 times. Among participants reporting signs, symptoms, diagnosis, and the management of kidney stones, the knowledge and understanding about kidney stones was high. However, the perceptions of the same cohort about dietary precautions were limited. While analysing the sources of knowledge, the Internet and mass media were twice as important as physicians in educating the population. Conclusion: This study shows that the study cohort from the UAE population was aware of certain aspects of kidney stones but was quite naïve about its consequential risk factors. This highlights the importance of promoting education about kidney stones through health campaigns.